1994
DOI: 10.3892/or_00000031
|View full text |Cite
|
Sign up to set email alerts
|

Expression of adiponectin receptors, AdipoR1 and AdipoR2, in normal colon epithelium and colon cancer tissue

Abstract: Abstract. Adiponectin is secreted by adipocytes and is a key hormone responsible for insulin sensitization. Recent studies have shown that plasma adiponectin is decreased in patients with breast, endometrial and gastric cancer. However, the effect of adiponectin on colorectal carcinogenesis is controversial. It is now well known that the adiponectin receptor exists in two isoforms, adiponectin receptor 1 (AdipoR1) and adiponectin receptor 2 (AdipoR2). We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 2 publications
0
50
4
2
Order By: Relevance
“…However, Lukanova et al did not identify any relationship between plasma adiponectin levels and CRC (Lukanova et al, 2006). Also, Yoneda et al showed that there was not any difference between normal colon epithelium and colorectal cancer tissues in Adipo-R1 or Adipo-R2 expression (Yoneda et al, 2008) We designed this study to elucidate whether there is a relationship between Adipo-R1/R2 expression and (Barresi et al, 2009) Another remarkable finding of our study was the demonstration of Adipo-R1/-R2 expression both in normal tissue and CRC tissue. We know that adiponectin acts via Adipo-R1/-R2 receptors and thus, based on our findings, we may suggest that adiponectin might have a protective effect against colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Lukanova et al did not identify any relationship between plasma adiponectin levels and CRC (Lukanova et al, 2006). Also, Yoneda et al showed that there was not any difference between normal colon epithelium and colorectal cancer tissues in Adipo-R1 or Adipo-R2 expression (Yoneda et al, 2008) We designed this study to elucidate whether there is a relationship between Adipo-R1/R2 expression and (Barresi et al, 2009) Another remarkable finding of our study was the demonstration of Adipo-R1/-R2 expression both in normal tissue and CRC tissue. We know that adiponectin acts via Adipo-R1/-R2 receptors and thus, based on our findings, we may suggest that adiponectin might have a protective effect against colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Yamauchi et al demonstrated that ApN acts via its two receptors, namely Adiponectin receptor-1 (Adipo-R1) and Adiponectin receptor-2 (Adipo-R2) (Yamauchi et al, 2003). In recent studies, the expression of Adipo-R1 and Adipo-R2 was shown immunohistochemically in human colorectal cancers (Williams et al, 2008;Yoneda et al, 2008). Currently, there are a few studies exist which addressed adiponectin receptor expression and its effects in colorectal cancer.…”
Section: Association Of Adiponectin Receptor (Adipo-r1/-r2) Expressiomentioning
confidence: 99%
“…Direct involvement of adiponectin in carcinogenesis is through action on cancer cells by contribution to cell proliferation and to the process of tissue remodeling (Tae et al, 2014). Low levels of adiponectin induce apoptosis and stimulate the process of cell polliferation by indirect destabilisation of glucose metabolism and insulin resistance (Kadowaki and Yamauchi, 2005;Yoneda et al, 2008). Hypoadiponectinemia may thus indicate a link between overweight and an increased risk of colorectal cancer.…”
Section: Obesity-leptin and Adiponectinmentioning
confidence: 99%
“…Adiponectin action is mediated by binding to two main receptors: adiponectin receptor 1 (AdipoR1) and receptor 2 (AdipoR2) (Kadowaki and Yamauchi, 2005). Adiponecitn has an impact on colorectal carcinogenesis by indirect and direct mechanisms (Yoneda et al, 2008;Gulcelik et al, 2012). In the indirect pathway, adiponectin acts through mediators such as insulin and proinflammatory factors.…”
Section: Obesity-leptin and Adiponectinmentioning
confidence: 99%
See 1 more Smart Citation